Effect of ultra-processed food consumption on male reproductive and metabolic health - Preston, Jessica M.; Iversen, Jo; Hufnagel, Antonia; Hjort, Line; Taylor, Jodie; Sanchez, Clara; George, Victoria; Hansen, Ann N.; Ängquist, Lars; Hermann, Susan; Craig, Jeffrey M.; Torekov, Signe; et al. (Cell Metabolism, 2025)
Consumption of ultra-processed food is associated with increased caloric intake and impaired health. Here, we conducted a nutrition trial (NCT05368194) with controlled, 2 × 2 crossover design and tested whether ultra-processed food impairs reproductive and metabolic fitness, with further aggravation by excess caloric intake. Comparing the response from an unprocessed to ultra-processed diet identified increased body weight and low-density lipoprotein (LDL):high-density lipoprotein (HDL) ratio, independent of caloric load. Several hormones involved in energy metabolism and spermatogenesis were affected, including decreased levels of growth/differentiation factor 15 and follicle-stimulating hormone. Sperm quality trended toward impairment, with a decrease in total motility. Differential accumulation of pollutants between the discordant diets were detected, such as decreased plasma lithium and a trend for increased levels of the phthalate mono(4-methyl-7-carboxyheptyl)phthalate (cxMINP) in serum, following the ultra-processed diet. Alteration in caloric load alone had distinct effects on the measured outcomes. This study provides evidence that consumption of ultra-processed food is detrimental for cardiometabolic and reproductive outcomes, regardless of excessive caloric intake.
Keywords: body weight management; cholesterol; depression score; diet intervention; hormones; phthalates; pollutants; reproduction; sperm quality; ultra-processed diet